Overview of the Quality of Service for Participants Using the Health Social Security Administering Body and Non-Health Social Security User Body at Hospital X - Rebeca Stevany Putri Patricia Hutajulu; Ria Efkelin; Hardin La Ramba (Lembaga Pengembangan Kinerja Dosen, 2025)
The quality of healthcare services is a crucial factor in determining patient satisfaction, particularly in the context of the implementation of the National Health Insurance (JKN) through the BPJS Health (Social Security Agency for Health). This study aims to describe the differences in healthcare service quality between BPJS and non-BPJS patients at Hospital X. Using a descriptive qualitative approach with SERVQUAL theory, data were collected through in-depth interviews and direct observation of the administrative service process. The results indicate a gap in service delivery, particularly in the dimensions of responsiveness and empathy. Non-BPJS patients tend to receive faster, friendlier, and more personalized service, while BPJS patients experience longer waiting times and less empathetic interactions with staff. These findings indicate that services at Hospital X do not fully reflect the principles of justice and equality. Improvements to the service system and staff competency are necessary to enhance the quality of care for all patients, regardless of insurance status.